HEAVY METALS ADSORPTION BY XANTHATE OF FOOD PROCESSING WASTE - Hartati, Indah (UMP, 2011)
Industrial effluent loaded with heavy metals are a cause of hazard to human and other forms of life. Conventional methods such as precipitation, evaporation, electroplating, ion exchange, membrane process used for removal of heavy metals from waste water however, are often cost prohibitive having inadequate efficiencies at low metal ion concentrations. Adsorption technology has become one of the alternative treatments. It is observed that appropriated modification of the raw adsorbents especially xanthates can eliminate the drawbacks of adsorbent and improve their performances significantly. Xanthates are most prominent because they are highly insoluble, easy to prepare with relatively inexpensive reagents and have high stability constant values of the metal complexes formed. Xanthates are formed by reacting an organic hydroxyl containing substrate with carbon disulfide under caustic condition. One of organic hydroxyl-containing substrate that can be used for xanthation is food processing waste. The major factors affect the biosorption process are: contact time, initial metal ion concentration, temperature, pH & biomass concentration in solution. It is postulated that metal ion adsorption process could undergo a complex formation. Most of heavy metal adsorption into the xanthate compound followed Langmuir adsorption isotherm model, and well described by the pseudo-second- order equation. Â Key-word : Adsorption, Xanthate, Heavy metal